Respuesta :
Answer:
See below in bold.
Step-by-step explanation:
(g + h)(x) = 4x - 4 + x - 5
= 5x - 9.
(g - h)(x) = 4x - 4 - (x - 5) ( Note we put the x - 5 in parentheses)
= 4x - 4 - x + 5
= 3x + 1.
(g.h)(x) = (4x - 4)(x - 5)
so (g.h)(1) = (4(1) - 4)(1 - 5)
= 0 * -4
= 0.
The product of the functions will be (g·h)(x) = 4x² – 24x + 20. At x = 1, the product of the functions is zero.
What is a function?
A statement, principle, or policy that creates the link between two variables is known as a function.
The functions are given below.
g(x) = 4x – 4
h(x) = x – 5
Then the sum of the functions will be
(g + h)(x) = (4x – 4) + (x – 5)
(g + h)(x) = 4x – 4 + x – 5
(g + h)(x) = 5x – 9
Then the difference in the functions will be
(g – h)(x) = (4x – 4) – (x – 5)
(g – h)(x) = 4x – 4 – x + 5
(g – h)(x) = 3x + 1
Then the product of the functions will be
(g·h)(x) = (4x – 4)(x – 5)
(g·h)(x) = 4x² – 4x – 20x + 20
(g·h)(x) = 4x² – 24x + 20
At x = 1, then we have
(g·h)(x) = 4(1)² – 24(1) + 20
(g·h)(x) = 4 - 24 + 20
(g·h)(x) = 0
More about the function link is given below.
https://brainly.com/question/5245372
#SPJ2